Synthesis and characterization of silver nanoparticles by Murraya Koenigii leaves - Sharma, Sandeep; Yadav, Deepak Kumar; Chawla, Kanhaiya; Lal, Nathu; Jain, Pankaj K.; Kumar, Sushant; Lal, Chhagan (Penerbit Universiti Kebangsaan Malaysia, 2022)
Nanoparticles have a size of 1nm-100nm in any one of the three dimensions. Smaller nanoparticles have different physical, chemical and biological properties than atoms and molecules. Metals, non-oxide ceramic materials, metal oxides, silicates, and polymers, and organic and biomolecular components can be used to create material nanoparticles. Nanoparticles come in various shapes, like spheres, platelets, cylinders, and tubes. Green synthesized nanoparticles are not costly due to unemployment of toxic and hazardous compounds. Plants are widely spread, freely accessible, and safe to touch. They also supply a variety of metabolic compounds which are advantageous in reducing, capping and stabilizing process throughout in synthesis process. The reduction mechanism is based on the phytochemicals present in plant extract. In present work we synthesize silver nanoparticles by using Murraya Koenigii leaves through ecofriendly method. For synthesis of Silver nanoparticles, Silver nitrate (AgNO3 ) used as metal precursor salt and green extract of Murraya Koenigii used as reducing and capping agent for formation of nanoparticles. The nanoparticles then formed characterized by X-ray diffraction, Scanning electron microscope, Energy dispersive spectroscopy, Dynamic light scattering, Fourier transform infrared spectroscopy and optical properties by UV-Visible spectroscopy. XRD revealed the crystalline structure of silver nanoparticles, FESEM and Dynamic light scattering reveled the particle size of 60 nm, FTIR revealed the presence of different functional groups which are attached with sample and Optical properties of sample revealed by UV-Visible spectroscopy that also satis ies different experimental results.